Commercial Potentials and Agronomic Status of Etlingera elatior, a Promising Horticulture Plant from Zingiberaceae Family - Muhamad Fahmi Yunus; Nor Asiah Ismail; Tamil Chelvan Meenakshi Sundram; Zarina Zainuddin; Norsalsabila Mohd Rosli (AGRIVITA, Journal of Agricultural Science, 2021)
Etlingera elatior or torch ginger is a species under the Zingiberaceae family, primarily distributed in tropical forests and humid, shady places. It is a coarse herb often growing in large colonies, characterized by elongated leafy stems up to 5 m height arising from underground rhizomes. It is known as kantan in Malaysia and kecombrang in Indonesia. The inflorescence is famous as an ingredient in Malay, Indonesian and Thai dishes. The extract from its stem is used to reduce swelling, and post-partum women use the leaves while the fruits are used to treat earache, diarrhea, coughs, and mouth sores. Because it has a beautiful appearance, it is also widely marketed as a promising floriculture and horticulture plant. Recently, the rising demand from customers for the versatility and durability of cut flowers has made farmers and the horticulture industry search for new cultivars. Thus, researchers are keen to generate cultivars with various colors, shapes, yields, and longer vase life. This could be done through different techniques such as intensive germplasm collection, hybridization programs, and plant biotechnology techniques. Towards achieving these aims, this review provides current insight on E. elatior from botanical, physiological growth, breeding, taxonomy, ecology, commercial potential, postharvest, medicinal, and food nutritional aspects.